Tantangan dan Solusi dalam Pengelolaan Pendidikan Modern - Shafira, Diva; Aditya, Ferdino Arief; Anggia, Intan Ratu; Putri, Nasya Nurlillah Kusuma; Hanif, Salman Al; Prihantini, Prihantini (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The management of modern education faces various challenges that continue to develop, especially in the face of technological changes and global needs. The education process now requires a more targeted approach, where various factors, including the quality of teaching, accessibility of education, and adaptation of the curriculum to the needs of the times, are increasingly becoming the main issues. This study uses a qualitative method that aims to describe the conditions that are occurring, the relationship between phenomena, views, processes, results, or certain tendencies in a context. The data collection techniques used are observation, literature study, and documentation. Literature Studies are conducted as a basis to analyze various perspectives and problem solving in education management in modern times. The data produced was analyzed in a qualitative descriptive manner. The results obtained from this study are that a series of solutions are needed which include the construction of equitable educational facilities, the use of technology that can reach remote areas, the improvement of teacher competence and welfare, and curriculum reform that is more responsive to the needs of the times and the world of work to realize the management of modern education in Indonesia